Composite cavitation resistant PVD coatings based on NiTi thin films. (15th November 2016) - Momeni, Soroush; Tillmann, Wolfgang; Pohl, Michael
Abstract: As a protective coating, TiCN hard PVD coating was deposited on magnetron sputtered NiTi thin films under various coating architectures. The microstructure, composition, mechanical properties, tribological performance as well as the cavitation resistance of deposited coatings were analyzed by using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), nanoindentation, ball–on-disc, scratch test, three dimensional (3D) optical microscopy, and the standard ultrasonic cavitation test (ASTM G 32). The obtained results revealed that under a specific coating architecture, the superelasticity of NiTi can be combined with high hardness and wear resistance of TiCN coatings. As a consequence of the combination of these properties, the composite NiTi based coatings are capable of presenting remarkable cavitation resistance and tribological performance. Graphical abstract: Highlights: Fabrication of composite coatings by combining superelasticity of sputtered NiTi thin films and the hardness of TiCN coatings. Tailoring mechanical properties of composite coatings by varying of the thickness of individual coating layers Calculation of modulus of resilience of composite coatings by using nanoindentation hardness and Young's modulus. Defining the correlation between the modulus of resilience of composite coating and their cavitation erosion resistance capability.